Model of physical activity during rehabilitation after myocardial infarction - Vovkodav, Oleksandr; Pasichnyk, Roman; Shpintal, Mykhailo; Honchar, Lyudmyla (Видавництво Львівської політехніки, 2012)
Effective rehabilitation requires a graduated exercise, existing mathematical models based on average data. The task is to identify the specific model organism.
Keywords: mathematical model; the cardiovascular system; heart rate; blood pressure